POTENTIAL OF RICE (Oryza spp.) STRAW AS FODDER FOR WEST AFRICAN DWARF SHEEP (2014)
Conventional feedstuffs have not met the increasing demand of livestock industry. Rice plant, a food-feed cereal, can provide grains for humans and fodder for livestock. The potential of Rice Straw (RS) as fodder for sheep in Nigeria has not been adequately documented. Therefore, the potential of RS as fodder for West African Dwarf (WAD) sheep was investigated in this study.